INTERNAL CONJUNCTION APPLICATION IN JAKARTA POST NEWS ABOUT GENDER - Desi Arintawati; Fiona Puspitasari; Desi Rohma (Universitas Duta Bangsa Surakarta, 2023)
Discourse is generally the way a person thinks and communicates with others. Discourse does not only share certain thoughts and meanings; there are many kinds of topics that can be discussed and analyzed. One of them is conjunction, which is a part of an utterance that is used to connect words, phrases, clauses, and sentences, which are divided into external and internal. Conjunctions have four types, namely addition, comparison, time, and effect. With the data source of four news texts selected by the Jakarta Post with the topic of Gender, this research has the aim of: To find out the internal conjunctions that exist in the Jakarta Post news texts as written discourse. 2). The method used is descriptive-qualitative, which produces twenty-nine pieces of data consisting of conjunctions of addition, time, consequence, and comparison. There are thirteen data points (44.8%) of addition conjunctions. Seven data points (24.2%) are time conjunctions, and four data points (13.8%) are consequence conjunctions. Finally, five data points (17.2%) are comparison conjunctions.